Revolutionizing Supply Chain Management: Internet of Things (IoT) and Machine Learning on Logistics Transparency and Efficiency in the Retail Industry in Indonesia - Judijanto, Loso; Parhusip , Jadiaman; Sumerli A. , Chevy Herli; Mu'min, Halek (West Science Interdisciplinary Studies, 2025)
The integration of Internet of Things (IoT) and Machine Learning (ML) technologies is transforming supply chain management, particularly in the retail industry. This study examines the impact of IoT implementation and ML application on logistics transparency and operational efficiency in Indonesia’s retail sector. Using a quantitative research approach, data were collected from 115 professionals and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that IoT and ML significantly enhance logistics transparency, which, in turn, positively influences operational efficiency. This study highlights the mediating role of logistics transparency and underscores the importance of leveraging digital technologies for improving supply chain performance. These findings provide actionable insights for stakeholders aiming to optimize their logistics operations in dynamic and competitive markets.